Molecular and biochemical characterization of the Neurospora crassa glycogen synthase encoded by the gsn cDNA - de Paula, R.; de Pinho, C. A.; Terenzi, H. F.; Bertolini, Maria Celia [UNESP] (Springer, 2002)
Glycogen synthases catalyze the transfer of a glucosyl moiety from a nucleotide phosphosugar to a nascent glycogen chain via an alpha1-->4 linkage. Although many genes coding for glycogen synthases have been described, the enzymes from rabbit and yeast are the best characterized. The fungus Neurospora crassa accumulates glycogen during exponential growth, and mobilizes it at the onset of stationary phase, or when placed at high temperature or starved for carbon. Through a PCR methodology, the gsn cDNA coding for the N. crassa glycogen synthase was isolated, and the amino acid sequence of the protein was deduced. The product of the cDNA seems to be the only glycogen synthase present in N. crassa. Characterization of the gsn cDNA revealed that it codes for a 706-amino acids protein, which is very similar to mammalian and yeast glycogen synthases. Gene expression increased during exponential growth, reaching its maximal level at the end of the exponential growth phase, which is consistent with the pattern of glycogen synthase activity and glycogen level. Expression of the gsn is highly regulated at the transcriptional level. Under culture conditions that induce heat shock, conidiation, and carbon starvation, expression of the gsn gene was decreased, and glycogen synthase activity and glycogen content behaved similarly.
Keywords: Neurospora crassa; cDNA; glycogen synthase activity; glycogen